2016
DOI: 10.1007/s00300-016-1986-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of changes in salinity on oxygen and food consumption of the young sub-Antarctic notothenioid Eleginops maclovinus: possible implications of their use of an estuarine habitat

Abstract: Salinity is one of the most important structuring factors in the distribution and bioenergetics of estuarine fishes. The aims of this work were to study the distribution of the sub-Antarctic, eurythermic, euryhaline and coastal notothenioid Eleginops maclovinus in Lapataia estuary (Tierra del Fuego National Park), in relation to salinity conditions, and the effect of salinity on the oxygen consumption of this species. The spread of the mixing zone of Lapataia was studied and physicochemical properties (conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
2
1
Order By: Relevance
“…Accordingly, and in good agreement with expected responses for ectotherm organisms with broad latitudinal distributions (Markle and Kozak, 2018), the SMR of juvenile E. maclovinus was significantly affected by increasing exposure temperature and by the interactive effect of temperature and pCO2. The SMR at 10 °C and present-day pCO2 levels in this study were slightly higher than rates previously measured in E. maclovinus by Vanella et al (2012Vanella et al ( , 2017. Such differences could result from different fish body masses between studies.…”
Section: Discussioncontrasting
confidence: 77%
“…Accordingly, and in good agreement with expected responses for ectotherm organisms with broad latitudinal distributions (Markle and Kozak, 2018), the SMR of juvenile E. maclovinus was significantly affected by increasing exposure temperature and by the interactive effect of temperature and pCO2. The SMR at 10 °C and present-day pCO2 levels in this study were slightly higher than rates previously measured in E. maclovinus by Vanella et al (2012Vanella et al ( , 2017. Such differences could result from different fish body masses between studies.…”
Section: Discussioncontrasting
confidence: 77%
“…For instance, juveniles of E . maclovinus have a faster growth rate in intermediate salinity environments (iso‐osmotic and hyperosmotic; Vargas‐Chacoff et al, 2015 ) and with food availability conditions (Vanella et al, 2017 ). Oxygen consumption as a proxy of metabolisms showed minor changes comparing gill and kidney tissues with liver tissue, suggesting that E .…”
Section: Discussionmentioning
confidence: 99%
“…maclovinus have a faster growth rate in intermediate salinity environments (iso-osmotic and hyperosmotic; Vargas-Chacoff et al, 2015) and with food availability conditions (Vanella et al, 2017). Oxygen consumption as a proxy of metabolisms showed minor changes comparing gill and kidney tissues with liver tissue, suggesting that studies have shown that E. maclovinus could reorganize components for the intermediary metabolism to respond to climate change (Oyarzún et al, 2017).…”
Section: Adaptive Variationmentioning
confidence: 98%